EFFICACY OF DHANYAMLA SARVANGA DHARA IN THE MANAGEMENT OF OBESITY: AN ANALYTICAL REVIEW - Chauhan, Vandana; Kumar Srivastava, Alok; Gusain, Meenakshi; Priyanka (International Journal of Ayurveda and Pharma Research, 2018)
Obesity consist a major nutritional health problem in developed and developing countries, which has reached epidemic proportions. It is a medical condition of excessive fat accumulation to the extent that it may have negative effect on health. Obesity are major causes of co-morbidities, including type 2 diabetes, cardiovascular disease, various cancer and other health problem like obstructive sleep apnea, osteoarthritis and depression. Obesity is most commonly caused by a combination of excessive food intake, lack of physical activity. Leptin enzyme is responsible for controlling appetite through its action on CNS, TNF alpha is also link factor between fat accumulation and metabolic disorders. The body mass index (BMI) is an internationally accepted index to estimate body weight. Taking medication like Sibutramine, Orlistat as an option for treatment of obesity can be given, because it is associated with many side effects. Bariatric surgery may be performed to reduce weight, but it is not very useful treatment. Diet, life style modification, physical activity can achieve the desired loss of body fat. In Ayurveda best treatment for Sthaulya defined by Acharyacharak and Sushruta and Vagbhatt. Dhanyamalasarvangadhara is highly effective in Vata associated with Ama and Kapha. Dhanyamla sarvanga dhara eliminates the body toxins, establishes health and tones up the joints and soft tissues. The drug will act soon as the medicine touches the skin surface. Due to Vasodilation property blood flow will increase through the area, increasing metabolism further eliminating the toxins, which will help in reducing the obesity. Dhanyamala sarvanga dhara controls the disease process and may cause long lasting relief.